Academic Senate Minutes 2009-02-19 - Academic Senate:::::::::
Certification of Election. Approval of Agenda. Approval of Minutes of 2/5 postponed. Provost Report. Associated Students Report. SSU Statement on Collegiality approved. Revision to the Biology Curriculum approved. Resolution on the CLA failed. Resolution on Emeriti first reading. CFA Report. Vice President of Administration and Finance Report. Report from the Ad-Hoc Diversity Committee